In-Vitro Bioequivalence of Amoxicillin and Clavulanic acid products available in Syrian market using Derivative Spectrophotometry - محمد مرح; بركات هلا; سلميان فاتن (Latakia University Journal -Medical Sciences Series, 2023)
Bioequivalence (BE) is an essential requirement for interchanging brand and generic drugs. It could be evaluated In Vivo or In Vitro, and should be carried out for all pharmaceutical products “single drug or combinated drugs”. For the latter, BE studies are often carried out by means of chromatographic methods (HPLC), where it is not possible to use spectrophotometry because of drugs that absorb at the same spectral region such as the binary mixture of amoxicillin and clavulanic acid. This study aimed to carry out BE test of Augmentin (Amoxicillin and Clavulanic acid) products manufactured and available in Syrian market by using Derivative spectrophotometry. First order and Zero-Crossing technique were used for simultaneous determination of these drugs. Three local companies A, B and C were tested and compared with the brand using dissolution test and calculating fit factors (dissimilarity factor ????1 and similarity factor ????2). Other quality control tests were carried out. All tablets achieved weight uniformity and had good hardness with a disintegration time of less than 30 minutes. Weight variation test (content of amoxicillin) was achieved for all samples, while content uniformity of clavulanic acid was not achieved. For dissolution test, only one sample was bioequivalent with brand (for amoxicillin), however no sample was bioequivalent (for clavulanic acid).